Features of Bacterial Microbiota in the Wild Habitat of Pulsatilla tongkangensis, the Endangered “Long-Sepal Donggang Pasque-Flower Plant,” Endemic to Karst Topography of Korea - Dutta, Swarnalee; Na, Chae Sun; Lee, Yong Hoon (Frontiers in Microbiology, 2021)
Microbes associated with plants significantly influence the development and health of the plants. The diversity and function of microbiomes associated with the long-sepal Donggang pasque-flower (DPF) plant, an endemic and endangered species in karst ecosystems, remain unexplored. In this study, we investigated the features of bacterial communities associated with the rhizosphere and roots of DPF plants and their functions in plant growth promotion. The DPF plants were collected from natural and cultivated habitats, and their 16S rDNA was sequenced to assess the bacterial community structures. The bacterial microbiota was more diverse in wild than in cultivated plants. The core bacterial microbiota commonly functioned as endophytes in both wild and cultivated DPF plants, although there were some differences. The identified bacterial strains benefited plants through nitrogen fixation, phosphate solubilization, or phytohormone production, inducing measurable growth differences in Arabidopsis thaliana. To the best of our knowledge, this study is the first to report the bacterial community structures associated with the rhizosphere soil and roots of DPF plants in karst ecosystems. The bacterial strains isolated in this study could be used to aid sustainable growth and restoration of rare plants in karst ecosystems. Our systematic research on the microbiomes associated with these endangered plants will contribute to their conservation as well as development of better cultivation.